Effects Of Blogs In Learning Computer Science Teacher’s At Namakkal District - P.Sasikala, Dr.K.Nachimuthu (Drugs and Cell Therapies in Hematology, 2021)
In this 21st century, the computer has made learning and teaching much easier. It has become inevitable for teachers to be selective in computer-based knowledge. In this digital world of computer technology, it is easy to get information that is unaccounted for. Information technology knowledge is essential for learners and educators to easily store information and download information when needed. Nowadays millions of books can be obtained at the fingertips in a matter of seconds and the required information can be selected from it in a matter of seconds.